Mentalizing Another's Visual World—A Novel Exploration via Motion Aftereffect - Yuan, Xuefei; Wang, Nanbo; Geng, Haiyan; Zhang, Shen (Frontiers in Psychology, 2017)
Past research on level 2 visual perspective-taking (VPT) has mostly focused on understanding the mental rotation involved when one adopts others’ perspective; the mechanisms underlying how the visual world of others is mentally represented remain unclear. In three studies, we addressed this question by adopting a novel VPT task with motion stimuli and exploring the aftereffect on motion discrimination from the self-perspective. Overall the results showed a facilitation aftereffect when participants were instructed to take the avatar’s perspective. Meanwhile, participants’ self-reported perspective-taking tendencies correlated with the aftereffect for both instructed and spontaneous VPT tasks, when the “to-be-adopted” perspective required the participants to mentally transform their self-body clockwise. Specifically, while facilitation was induced for participants with low self-reported perspective-taking tendencies (e.g. viewing a leftward motion stimulus under another’s perspective enhanced subsequent perception of leftward motion from the self-perspective), those with high self-reported perspective-taking tendencies showed an adaptation aftereffect (e.g. viewing a leftward motion stimulus under another’s perspective weakened subsequent perception of leftward motion from the self-perspective). For these individuals, the adaptation effect indicated the engagement of direction-selective neurons in processing of the subsequent congruent-direction motion from self's perspective. These findings suggest that motion perception from different perspectives (self vs. another) may share the same direction-selective neural circuitry, and this possibility depends on observers' general perspective-taking tendencies.